EVOLUTION EXISTS, AT LEAST IN MUSICAL INSTRUMENTS - Massimo de Bonfils,; Mauro Fabretti, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Charles Darwin could have more successfully applied his theory of evolution to the technological development evident in Musical Instruments. Even the modern violin, so apparently similar to that of the 1600s, has actually been largely modified and for reasons similar to those that Darwin wanted to attribute to the origin of the species. Following his logic, what will the Violin of the future be? The new ergonomic violin model developed by the Santa Cecilia Conservatory in Rome may be the answer. Let us consider the concerto for violin and orchestra. From the Baroque era to Mozart, then from Beethoven to Tchaikovsky up to Sibelius and Khachaturian, the solo violinist had to deal with ever increasing acoustic needs that over time have been satisfied by continuous changes and updates in the construction of violins. Even the greatness of the theaters and the way in which the music was written progressively required more and more power and higher quality of sound: will classical lutherie be able to answer? The laboratory of the Lutherie Course of the Santa Cecilia Conservatory in Rome has created a new ergonomic model of violin that was conceived with the express purpose of producing more sound with a richer timbre. We are pleased to present it in this article.